Analisis Karakteristik Penumpang Kereta Cepat Jakarta Bandung (Whoosh) di Stasiun Halim - Fadhil, Dimas Nu'Man; Siahaan, Langas Denny; Shandy, Antika Tiara (Institut Transportasi dan Logistik Trisakti, 2023)
In Indonesia, a new rail-based transportation mode has recently been introduced, namely the Jakarta-Bandung High-Speed Rail (KCJB), commonly known as